Vyaṅgaviśva - Trivedī, Jagadīśa,Chhabda, Satpalsingh (Maulik Prakashan, 2012)
Humorous and satirical articles based on social and political themes
Humors and satires. - In Gujarati-Schr
Keywords: Political satire; Gujarati; Gujarati wit and humor